Adult social care in England: What next? - Antonella Bancalari; Ben Zaranko (Institute for Fiscal Studies (IFS), 2024)
We set out the major challenges facing the adult social care system in England and explore potential future developments for the sector.
Keywords: 330; Health and social care; Government spending; Local government finance; Social care